Robert B. Parker's Slow burn - Atkins, Ace; Parker, Robert B., 1932-2010 (2016)
Boston PI Spenser is approached by firefighter Jack McGee, who's convinced that the apartment blaze that took the lives of five residents and two firefighters was arson.
Map on endpapers.
Keywords: Spenser (Fictitious character) -- Fiction; Private investigators -- Massachusetts -- Boston -- Fiction; Arson -- Massachusetts -- Boston -- Fiction; Boston (Mass.) -- Fiction; Mystery fiction